2005
DOI: 10.1038/sj.pcan.4500817
|View full text |Cite
|
Sign up to set email alerts
|

Expression of thymidylate synthase, dihydropyrimidine dehydrogenase, thymidine phosphorylase, and orotate phosphoribosyl transferase in prostate cancer

Abstract: The enzymes thymidylate synthase (TS), dihydropyrimidine dehydrogenase (DPD), thymidine phosphorylase (TP), and orotate phosphoribosyl transferase (OPRT) are involved in the metabolism of the anticancer drug 5-fluorouracil. No reports have examined the expression of these enzymes in prostate cancer (CaP). A total of 25 previously untreated, hormone-sensitive CaP tissue samples and 11 benign prostatic hyperplasia (BPH) specimens were examined. Tissue of CaP and BPH tissue samples were obtained from formalin-fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The main feature of this method is the measurement of gene expression by real-time technology combined with LCM. 5,6 This technique allows the extraction of cancer cells from a small sample and the possibility of quantitative analysis. We analyzed gene expressions in samples of gallbladder cancer from our patient using this method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main feature of this method is the measurement of gene expression by real-time technology combined with LCM. 5,6 This technique allows the extraction of cancer cells from a small sample and the possibility of quantitative analysis. We analyzed gene expressions in samples of gallbladder cancer from our patient using this method.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes were all measured by Response Genetic (Los Angeles, CA, USA), according to the DTP method, with laser-capture microdissection (LCM), as previously described. 5,6 Intratumoral DPD and OPRT gene expressions were high. On the other hand, TS gene expression was lower than that found in normal tissue (Table 1).…”
Section: Case Reportmentioning
confidence: 97%
“…The degree of thymidylate synthase (TS), DPD and OPRT protein expression is thought to be one of the most reliable factors. Many studies have reported that various carcinomas with higher expression of TS, DPD and lower expression of OPRT may resist 5-FUbased chemotherapy (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Microdissection A representative formalin-fi xed, paraffi n-embedded tumor specimen was selected by a pathologist after the examination of hematoxylin and eosin-stained slides. Ten-micronthick sections were stained with neutral fast red to enable visualization of histology for laser capture microdissection (P.A.L.M.…”
Section: Measurement Of Tp Gene Expressionmentioning
confidence: 99%